Can Children Be Considered for Transradial Interventions?: Prospective Study of Sonographic Radial Artery Diameters. (July 2020) - Alehaideb, Ahmad; Ha, Winston; Bickford, Suzanne; Dmytriw, Adam A.; Bhatia, Kartik; Amirabadi, Afsaneh; Mohanta, Arun; Chavhan, Govind; Muthusami, Prakash
Abstract : Background: Transradial intervention is increasingly replacing approaches, due to lower access complications, cost, and improved patient satisfaction. There are limited supporting data in the pediatric literature, largely due to concerns regarding arterial size. The objective of this study was to measure radial artery diameters in children across all age groups, to establish reference ranges for clinical use. Methods: This prospective study was carried out in children ⩽18 years of age who underwent ultrasound for measuring radial artery diameters from November 2018 to November 2019. The cohort was divided into age groups: ⩽2, 3 to 5, 6 to 8, 9 to 11, 12 to 14, 15 to 18 years, and into pre- and post-adolescent (≥12 years) groups. Results: One hundred thirty-four children (M:F=63:71) were included, with bilateral measurements resulting in 268 data points. Mean age was 8.9±5.8 years (range, 29 days to 18 years), mean weight 37.2±27.5 kg (range, 1.7–149.1 kg). Mean-corrected radial artery diameter was 1.86±0.44 mm. There was no difference in arterial diameters between males and females (1.90±0.50 versus 1.81±0.53 mm; P =0.73) or between right and left sides (1.87±0.46 versus 1.87±0.47, P =0.98). There was a strong correlation of diameter with age (R=0.75; P <0.00001) and weight (R=0.74; P <0.00001). There was linear increase in arterial growth rates in early childhood, followed by plateauing to adult sizes in adolescents. Inter-reader agreement was 0.95. Conclusions: We provide a reference range for radial artery diameters across childhood ages, which can be used for decision-making. This could be the basis for designing a trial of transradial intervention in children, to establish clinical safety and efficacy.